2008
DOI: 10.2337/db08-0326
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-Associated Protein Association With Src Homology 2 Domain Containing Tyrosine Phosphatase Substrate 1 Regulates IGF-I Signaling In Vivo

Abstract: OBJECTIVE-Smooth muscle cell (SMC) maintained in medium containing normal levels of glucose do not proliferate in response to IGF-I, whereas cells maintained in medium containing 25 mmol/l glucose can respond. The aim of this study was to determine whether signaling events that have been shown to be required for stimulation of SMC growth were regulated by glucose concentrations in vivo. RESEARCH DESIGN AND METHODS-We compared IGF-Istimulated signaling events and growth in the aortic smooth muscle cells from no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 37 publications
(48 reference statements)
5
28
0
Order By: Relevance
“…Our prior studies have shown that when IRS-1 levels are substantially increased (e.g. VSMCs maintained in 5 mM glucose), SHPS-1 phosphorylation, SHP-2 transfer, and Shc/MAPK activation are suppressed (29,70). Consequently, although the protein synthesis response to IGF-I is maintained, the cell migration and proliferation responses are significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our prior studies have shown that when IRS-1 levels are substantially increased (e.g. VSMCs maintained in 5 mM glucose), SHPS-1 phosphorylation, SHP-2 transfer, and Shc/MAPK activation are suppressed (29,70). Consequently, although the protein synthesis response to IGF-I is maintained, the cell migration and proliferation responses are significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…In normal mice, VSMCs are maintained in the quiescent state (71,72) and have a minimal proliferative response to IGF-I administration. In contrast, the presence of diabetes cell proliferation is increased substantially (70). Because differentiated VSMCs in blood vessels are maintained in a non-proliferative state, expression of IRS-1 may be one of the important determinants that allow normal protein synthesis and hypertrophic responses to IGF-I and insulin while functioning simultaneously to inhibit cell replication.…”
Section: Discussionmentioning
confidence: 99%
“…TSP1 also interacts with ␣ v ␤ 3 -integrin through CD47 (integrin-associated protein) impacting VSMC adhesion and migration (21). Furthermore, expression of CD47 and its interaction with TSP1 have been shown to be important in the proliferative and migratory responses of VSMCs to IGF-I (30). However, the role of these interactions in the modulation of retinal PC adhesion and migration requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia was induced in C57/B6 mice (Taconic, Hudson, NY) using the low dose streptozotocin protocol previously described (20). Briefly, after withdrawal of food for 4 h, the mice were injected intraperitoneally with streptozotocin (50 mg/kg) (n ϭ 72) daily for 5 days.…”
Section: Methodsmentioning
confidence: 99%